The Future of Consumption How Technology, Sustainability and Wellbeing will Transform Retail and Customer Experience - Bäckström, Kristina; Egan-Wyer, Carys; Samsioe, Emma (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
"Fascinating contemporary perspectives on the nexus between retailing and consumption." - Jonathan Reynolds, University of Oxford "An invaluable resource for individuals who are eager to stay ahead in the ever-evolving world of retail and consumption." - Sofia Norén, Chief Business Development Officer, Storekey "An interesting read with inspiring examples and best-practises that can inspire to action. " - Jesper Brodin, CEO Ingka Group IKEA This open access book presents three future consumption trends-technology, sustainability, and wellbeing-and discusses what impact those trends will have on the ways we shop. What will be important to the consumers of the future? And how will their retail experiences look and feel? Will technology, sustainability, and wellbeing trends fundamentally change how we consume? And how should retail managers respond to these trends in order to provide the customer experiences of the future? Blending academic perspectives with reflections from innovative retailers, this book explores all these questions and more. Essential reading for retail managers who want to know how future consumption trends will affect the industry, this book also benefits students and researchers of retail and consumption who want to better understand how these interdependent fields are linked. Kristina Bäckström is a Senior Lecturer at the Department of Service Studies & Centre for Retail Research, Lund University. Carys Egan-Wyer is a Senior Lecturer at the Department of Business Administration & Centre for Retail Research, Lund University. Emma Samsioe is an Associate Senior Lecturer at the Department of Service Studies & Centre for Retail Research, Lund University.